Influence Decrease in Chemical Oxygen Demand (COD) Against Biogas Quality and Production - Eko Supriadi; Ailsya Nadya Rizki (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Chemical Oxygen Demand or Need Oxygen chemistry is amount oxygen is needed for waste organic matter in the water can​ oxidized in a way chemistry . Chemical Oxygen Demand (COD ) have the value which is size For level pollution by material organic . COD value contained in material standard such as palm oil mill effluent can converted into biogas due to its high value so that allow For produce high biogas production . On study This done data collection in direct that is with using secondary data and primary data. From the research that has been done , known that The more high COD Removal then the more The quality of the methane gas produced is also high . This is can seen based on at COD removal of 81%, it was obtained methane gas quality by 67%. And, increasingly high COD lowered so the more The biogas production produced is also high . This is can seen based on on COD reduction of 797,716 kg resulted in biogas production of 478,629 m3.